Production of 3D Printed Bi-Layer and Tri-Layer Sandwich Scaffolds with Polycaprolactone and Poly (vinyl alcohol)-Metformin towards Diabetic Wound Healing - ŞAHİN, ALİ (My University, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic disease characterized by impaired insulin secretion, sensitivity, and hyperglycemia. Diabetic wounds are one of the significant complications of T2DM owing to its difficulty in normal healing, resulting in chronic wounds. In the present work, PCL/PVA, PCL/PVA/PCL, and metformin-loaded, PCL/PVA-Met and PCL/PVA-Met/PCL hybrid scaffolds with different designs were fabricated using 3D printing. The porosity and morphological analysis of 3D-printed scaffolds were performed using scanning electron microscopy (SEM). The scaffolds’ average pore sizes were between 63.6 ± 4.0 and 112.9 ± 3.0 µm. Molecular and chemical interactions between polymers and the drug were investigated with Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). Mechanical, thermal, and degradation analysis of the scaffolds were undertaken to investigate the physico-chemical characteristics of the scaffolds. Owing to the structure, PCL/PVA/PCL sandwich scaffolds had lower degradation rates than the bi-layer scaffolds. The drug release of the metformin-loaded scaffolds was evaluated with UV spectrometry, and the biocompatibility of the scaffolds on fibroblast cells was determined by cell culture analysis. The drug release in the PCL/PVA-Met scaffold was sustained till six days, whereas in the PCL/PVA-Met/PCL, it continued for 31 days. In the study of drug release kinetics, PCL/PVAMet and PCL/PVA-Met/PCL scaffolds showed the highest correlation coefficients (R2 ) values for the first-order release model at 0.8735 and 0.889, respectively. Since the layered structures in the literature are mainly obtained with the electrospun fiber structures, these biocompatible sandwich scaffolds, produced for the first time with 3D-printing technology, may offer an alternative to existing drug delivery systems and may be a promising candidate for enhancing diabetic wound healing.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; POLİMER BİLİMİ; Temel Bilimler (SCI); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; metformin; diabetic wound healing; drug release; 3D-printed scaffold; sandwich scaffolds; METFORMIN HYDROCHLORIDE; NANOFIBROUS SCAFFOLDS; CONTROLLED-RELEASE; TISSUE; FABRICATION; DRESSINGS; COMPOSITES; CHITOSAN; GELATIN; metformin; diabetic wound healing; drug release; 3D-printed scaffold; sandwich scaffolds